Why high grain yield can be achieved in single seedling machine-transplanted hybrid rice under dense planting conditions? - Min HUANG; Shuang-lü SHAN; Xiao-bing XIE; Fang-bo CAO; Ying-bin ZOU (Journal of Integrative Agriculture, 2018)
This study was conducted to identify the factors associated with high grain yield in single seedling machine-transplanted hybrid rice under dense planting conditions. Field experiments were done in Yong'an Town, Hunan Province, China in 2015 and 2016. Two hybrid rice cultivars were grown under single seedling machine transplanting (SMT) and conventional machine transplanting (CMT) at a high planting density in each year. Grain yield and yield attributes were compared between SMT and CMT. Averaged across cultivars and years, grain yield was 12% higher under SMT than under CMT. Plant height, basal stem width, and shoot and root dry weights were higher in seedlings for SMT than those for CMT. SMT had less maximum tiller number per m2 and consequently less panicle number per m2 than did CMT. Branch number per panicle, especially the secondary branch number per panicle, and spikelet number per cm of panicle length were more under SMT than under CMT, which resulted in more spikelet number per panicle under SMT than under CMT. SMT had higher or equal spikelet filling percentage than did CMT. The difference in grain weight between SMT and CMT was relatively small and inconsistent cross years. SMT had higher or equal total biomass and harvest index than did CMT. Dry weight per stem under SMT was heavier than that under CMT. Larger leaf area per stem was partly responsible for the heavier dry weight per stem under SMT than under CMT. Our study suggests that improvement in seedling quality, panicle size, and dry weight per stem are critical to the high grain yield in single seedling machine-transplanted hybrid rice under dense planting conditions.